2015
DOI: 10.1021/acs.inorgchem.5b01500
|View full text |Cite
|
Sign up to set email alerts
|

C–H Bond Oxidation Catalyzed by an Imine-Based Iron Complex: A Mechanistic Insight

Abstract: A family of imine-based nonheme iron(II) complexes (LX)2Fe(OTf)2 has been prepared, characterized, and employed as C-H oxidation catalysts. Ligands LX (X = 1, 2, 3, and 4) stand for tridentate imine ligands resulting from spontaneous condensation of 2-pycolyl-amine and 4-substituted-2-picolyl aldehydes. Fast and quantitative formation of the complex occurs just upon mixing aldehyde, amine, and Fe(OTf)2 in a 2:2:1 ratio in acetonitrile solution. The solid-state structures of (L1)2Fe(OTf)(ClO4) and (L3)2Fe(OTf)2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 88 publications
3
36
0
Order By: Relevance
“…However our data is higher than the value obtained in radical based oxidation reactions. This also supports that it is a metal based oxidation reaction [61][62][63][64][65][66]. It is interesting to note that the copper complex described in our previous report [33] the substrate and radical species convert the reactant into the corresponding product [79].…”
Section: Methodssupporting
confidence: 79%
“…However our data is higher than the value obtained in radical based oxidation reactions. This also supports that it is a metal based oxidation reaction [61][62][63][64][65][66]. It is interesting to note that the copper complex described in our previous report [33] the substrate and radical species convert the reactant into the corresponding product [79].…”
Section: Methodssupporting
confidence: 79%
“…The percentage conversion and TON has been shown in Table . On the basis of A/K ratio, it was found that our complexes provided good catalytic activity as compared to the results reported by Stefano and coworkers however less efficient than the catalysts reported by Que and coworkers . (As shown in Table ).…”
Section: Resultssupporting
confidence: 61%
“…Stefano and co‐workers recently reported oxidation of hydrocarbons by using mononuclear iron complexes derived from tridentate meridional ligands. In the mechanism of the reaction hexacoordinated iron was found to be pentacoordinated with the dissociation of one of the Fe‐N bonds during the reaction with hydrogen peroxide was reported and an intermediate iron complex having Fe IV =O moiety was generated …”
Section: Introductionmentioning
confidence: 99%
“…The so-called Shul'pin method [257][258][259] of analysis of oxygenates discussed above in this section and based on GC and PPh3 has been used by other authors (selected examples are given in Refs. [260][261][262][263][264][265][266][267][268][269][270][271][272][273][274][275][276][277][278]).…”
Section: Chromatograph With Clean Detector And/or Non-polar Columnsmentioning
confidence: 99%